The New Production of Expert Knowledge Education, Quantification and Utopia - Grek, Sotiria (Palgrave Studies in Science, Knowledge and Policy,, 2024)
This Open Access book offers a novel perspective on the role of quantification in the making of education utopias through an analysis of expert knowledge and its producers. Drawing on empirical findings from the European Research Council funded project 'International Organisations and the Rise of a Global Metrological Field' (METRO, 2017-2022), Education, Quantification and Utopia focuses on the ways that metrological realism has constructed a well-supported epistemic infrastructure, built on relationships and practices that go beyond the mere objectivity and reliability of numerical evidence. The book's chapters outline how the production of new forms of education expertise have led to ideational and institutional interdependencies, and ultimately the making of an intricate, fragmented and opaque knowledge and governance web. Sotiria Grek is Professor of European and Global Education Governance at the School of Social and Political Science, University of Edinburgh. She works on education policy, transnational policy learning, and the politics of quantification, knowledge, and governance. She is the Principal Investigator of the European Research Council funded project "International Organisations and the Rise of a Global Metrological Field" (METRO). She has recently co-authored 'Governing the Sustainable Development Goals: Quantification in Global Public Policy' (Springer 2022) and co-edited World Yearbook of Education 2021: Accountability and Datafication in Education (Routledge 2020).